Clinicopathological study on squamous cell carcinoma of the upper alveolus and gingiva and hard palate - Ogura, Ichiro; Okada, Norihiko; Yamashiro, Masasi; Iwaki, Hiroshi; Yoshimasu, Hidemi; Miyakura, Tsuyoshi; Amagasa, Teruo; Wadamori, Tadashi; Yamada, Takafumi; Ishikawa, Hitoshi (Journal of Japanese Society of Oral Oncology, 1997)
Clinicopathological study was performed to investigate squamous cell carcinoma of the upper alveolus and gingiva and hard palate. From 1980 to 1994, 45 cases of primary squamous cell carinomas were examined. There were 7 (15.6 %) cases of T1, 15 (33.3 %) cases of T2, 9 (20.0%) cases of T3, and 14 (31.1 %) cases of T4 by TNM classification. Combination therapy of the surgery, radiation, and chemotherapy were chosen in 24 (53.2%) of the cases. The 5-year cumulative survival rate in total cases was 58.9 % (80.0 % in cases of T1, 83.6 % in cases of T2, 40.0% in cases of T3 and 42.8 % in cases of T4) and 60.7 % in combination therapy. By pathological examinations, there was a close correlation between Y-K classification of behavior and suvival rate. The cumulative 5-year survival rate was 66.6% in cases of Y-K 1-3 and 33.3% in cases of Y-K4C, 4D. By classification of pattern of tumor invasion into alveolar bone and sinus, the cumulative 5-year survival rate was 100.0 % in cases of noninvasive type, 57.1 % in cases of alveolar bone invasion type (p<0. 05) and 44.4% in cases of sinus invasion type (p<0.01) . These results suggested that invasion types of the primary pathological specimen and pattern of invasion into alveolar bone and sinus may influence convalescence of squamous cell carcinomas of the upper alveolus and gingiva and hard palate.